Momfluencers as Digital Entrepreneurs: Social Media, Economic Empowerment, and Challenges in Indonesia - Dwityas, Nindyta Aisyah; Wahyuni , Hermin Indah; Andarwati , Siti (Journal of Sustainable Economic and Business, 2025)
Objectives: The rise of digital entrepreneurship has transformed women's economic participation, particularly among stay-at-home mothers who leverage social media platforms such as Instagram, TikTok, and YouTube for income generation. These platforms offer low-barrier entry into entrepreneurship, enabling women to monetize content, engage in brand collaborations, and establish online businesses with minimal financial investment. However, despite these opportunities, women digitalpreneurs remain vulnerable to algorithm dependency, engagement fluctuations, monetization uncertainty, and the dual burden of domestic and digital labor. Methodology: This study explores how social media entrepreneurship empowers Indonesian women economically while exposing them to structural challenges. Using a qualitative case study approach, it analyzes data from semi-structured interviews with momfluencers, mombloggers, and digital entrepreneurs, complemented by content analysis of social media engagement strategies. Findings: It reveals that while digital entrepreneurship provides financial independence and professional growth, women face precarious income streams, opaque platform policies, and intensified gendered labor expectations. Conclusion: The study highlights the urgent need for platform accountability, transparent monetization policies, and labor protections to ensure sustainable income opportunities. It contributes to global discussions on gendered digital labor and social media economies, emphasizing the importance of policy interventions and structural reforms for a more inclusive digital business landscape.